Cannabis use prevalence among primary and secondary school children in Turkey - Ögel, Kültegin; Uğuz, Şükrü; Sır, Aytekin; Yenilmez, Çınar; Tamar, Müge; Çorapçıoğlu, Aytül; Doğan, Orhan; Tot, Şenel; Bilici, Mustafa; Tamar, Defne; Evren, Cüneyt; Liman, Olcay (Journal of Dependence, 2003)
Objective: In this research, our objective was to find out the prevalence of cannabis use among primary and secondary school students, the characteristics of cannabis users, attitudes towards cannabis and behaviour patterns among cannabis users. Method: The study was conducted in 9 big cities of from different regions of Turkey. A self-rating form was applied to 11.989 primary and 12.270 secondary school children. Results: It was found that the existence of cannabis use was 1.2% among primary school students and 4% among secondary school students. The prevalence of cannabis use prevalence was three times higher in boys than girls. No significant differences were found, regarding the socioeconomic status of the families whose children used cannabis. The average age of cannabis use for the first time were 12.8±1.6 years among primary school students. This average was 12.7± 1.3 years for females and 12.9± 1.7 years for males. The average age of to cannabis use for the first time among secondary school students was 13.8± 1.9, 14.0± 1.8 years in females and 13.7± 1.9 years in males. Cigarette, smoking, the use of alcohol and other drugs more prevalent among the cannabis users. Conclusion: We found that cannabis use among males was higher and use of other drugs was common among the cannabis users. It was also found that environment had an effect on cannabis use.